Ground and excited state properties of alizarin and its isomers - Mech, Justyna (2014)
Four different alizarin dyes are studied with optical, electrochemical and quantum-chemical techniques. Despite structural similarities they show marked differences regarding both ground and excited state properties. All these dyes are characterized with strong HOMO–LUMO transitions of internal charge transfer character. These transitions, however, show different reorganization energies due to involvement of intramolecular proton transfer processes. Differences in charge redistribution upon excitation may lead to different photochemical reactivity of these species and also to different behavior in dye-sensitized solar cells and other devices.